Adjacency Pairs in Ellen DeGeneres’ Talk Show - Weby Yolannisa (Department of Indonesian Language Education, Graduate School, University of Muhammadiyah Prof. DR. HAMKA, 2019)
Talk Show is a program that basically deals with a conversational discussion concerning latest events in different aspects of life; social, economy, education, life style, love- life etc. From the conversation uttered by speakers, there are some patterns that they automatically produced, called adjacency pairs. Therefore, this study focused on the adjacency pairs in the conversation between the host (Ellen De’Generes) and the guest (Bill Gates) in Ellen De’Generes’ Talk Show. The aims of the research were (1) to describe and analyze types of adjacency pairs in the conversation between Ellen DeGeneres and Bill Gates, and (2) to describe and analyze the preference structure of adjacency pairs in the conversation between Ellen DeGeneres and Bill Gates. The main data of the research were the video and the script of the conversation between Ellen De’Generes and Bill Gates. This study used qualitative approach in investigating the problem in order to get the descriptive data after spoken and written data have been analyzed. In analyzing adjacency pairs and the preference structure of adjacency pairs, the researcher used the theory of conversation analysis (CA) as the basic theory. From the data, it was found that there were 11 adjacency pairs that consisted of 1 pair of assessment – agreement, 2 pair of assertion – agreement, 1 pair of assertion-disagreement, 6 pairs of question-answer, and 1 pair suggestion-acceptance in the conversation. Last, there were 11 data of the preference structure which consisted of 10 data included into the preferred structure from second pair part and 1 data included into the dispreferred structure from second pair part.